Educational Perspectives on the #KaburAjaDulu Phenomenon and Youth Social Behavior in Indonesia - Syifa Nur Syiami; Irawati (Journal of Smart Pedagogy and Education, 2025)
This research investigates the viral #KaburAjaDulu phenomenon in Indonesia as a critical response to socio-economic crises in 2025. Employing digital ethnography and systematic literature review, the study analyzes how legislative shocks, specifically Inpres No. 1/2025, and economic instability drive youth toward migration. Applying Stag Hunt game theory and Bourdieu’s cultural capital, it identifies a "defection equilibrium" where skilled individuals prioritize individual survival over national development due to institutional mistrust. Findings indicate that digital escapism and behaviors such as doom spending serve as precursors to physical migration intentions. The study contends that the current educational framework inadvertently facilitates brain drain by providing portable skills without domestic infrastructure. It proposes a systemic shift toward culturally mediated Social-Emotional Learning (SEL) and labor reforms to restore public trust. Ultimately, #KaburAjaDulu serves as a diagnostic indicator for policymakers, highlighting the urgent necessity to transform "escape" into a viable choice through structural and pedagogical strategic enhancements.